Wise Up: Creating Organizational Wisdom Through an Ethic of Kaitiakitanga - Spiller, Chellie; Pio, Edwina; Erakovic, Lijijana; Henare, Manuka (2011)
Organizations are searching for innovative business approaches that deliver profits and create shared value for all stakeholders. We show what can be learned from the relational wisdom approach of Indigenous Māori and reframe the prevailing economic argument that has seen companies profit and prosper at the expense of communities and ecologies. We develop an ethic of kaitiakitanga model premised on Māori values which holds the potential to enrich and further humanize our understanding of business. The Māori economy is a globally connected, prosperous, and profitable sector of the New Zealand economy. By drawing on Māori values, we present a wisdom position through an ethic of kaitiakitanga or stewardship to emphasize and illustrate the interconnectedness of life in a woven universe. Through practicing kaitiakitanga, organizations can build businesses where wisdom is consciously created through reciprocal relationships. In this worldview of business, humans are stewards endowed with a mandate to use the agency of their mana (spiritual power, authority, and sovereignty) to create mauri ora (conscious well-being) for humans and ecosystems—and this commitment extends to organizations.
Keywords: Wisdom; Well-being; Values; Stewardship; Maori; Indigenous; Ethics